Strategi Distribusi Produk Bawang Crispy di PT. Sinergi Brebes Inovatif - Fauziah, Sarah; Nur Utami, Suci; Khotimah, Khusnul (Universitas Muhadi Setiabudi, 2023)
PT. Brebes Innovative Synergy is a company operating in the agricultural sector, a company owned and managed by a farmer group, namely the Sidomakmur Farmer Group, which produces processed shallots. PT. Innovative Brebes Synergy is the first factory or production site in Brebes located in Sidamulya Village, Wanasari District, Brebes Regency, Central Java, which is built by the Bank Indonesia (BI) Tegal Representative Office. This company has processed red onions into red onion paste, fried onions and crispy onions which have reached export level to Jeddah and Singapore. PT. Brebes Innovative Synergy has problems related to product distribution. Moreover, after Covid-19 entered Indonesia, export-import activities were very limited. This causes a decrease in production and consumer output. This observation is intended to determine the distribution strategy at PT. Innovative Brebes Synergy using direct and indirect distribution. Based on observations during Field Work Practices, the author found two distribution strategies for Crispy Onion products at PT. Innovative Brebes Synergy, namely direct and indirect distribution. Distribution strategy is a company's effort to determine the distribution channels used to deliver products to consumers. By knowing the distribution strategy at PT. Innovative Brebes Synergy is expected to increase the quantity of consumers. To find out the distribution strategy, the author made observations. The observation that the author has made is by conducting a direct survey on product distribution activities and existing data.